Dissecting hydrogen bond energetics to answer the age-old question: “How much do hydrogen bonds contribute to enzymatic catalysis?” - Margaux M. Pinney; Corey Liu; Daniel Herschlag (Proceedings of the National Academy of Sciences, 2026)
Enzymes are fundamental to life, providing the rapid reactions and specificity needed to sustain biological processes. While we have overcome the first major challenge in understanding enzymes—identifying their reaction mechanisms—the second major challenge of quantifying the contributions of each catalytic interaction and molecular mechanism remains largely unmet. In particular, hydrogen bonds are ubiquitous in enzyme active sites, yet their quantitative contributions to enzyme catalysis have remained a fundamental unresolved question. We first describe the limitations that prevent the assignment of hydrogen bond catalytic contributions from traditional approaches. These limitations are overcome by using linear free energy relationships (LFERs) to evaluate active site hydrogen bond energetics in a particularly amenable enzyme, ketosteroid isomerase (KSI). Multiple LFERs provide a consistent picture, suggesting that KSI’s active site hydrogen bond donors, tyrosine and protonated aspartic acid side chains, contribute to catalysis because they are inherently stronger hydrogen bond donors than water molecules, the donors in the analogous nonenzymatic reaction. These LFERs also provide evidence against models that invoke distinct enzyme environments that enhance hydrogen bond energetics, relative to aqueous solution. Instead, the LFERs suggest multiple dipoles in the protein and solvent environment surrounding the active site accommodate transition state charge accumulation and provide hydrogen bond energetics similar to what is observed in protic solvents. The quantitative models from this and prior studies allow us to quantitatively estimate the catalytic contributions changes from hydrogen bonds. This model, applied to additional enzymes, will test its generality and help identify additional mechanisms that enzymes may use to enhance catalysis.